Transformers for GUI Testing: A Plausible Solution to Automated Test Case Generation and Flaky Tests. - Khaliq, Zubair; Farooq, Sheikh Umar; Khan, Dawood Ashraf (Computer (00189162), 2022)
Artificial intelligence has made significant progress in software testing as it is being incorporated into all stages of the software test lifecycle (STLC). However, formidable challenges remain within software testing activities in the STLC.